2002
DOI: 10.1159/000047757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Glycaemic Index on Clinical Outcome after Acute Stroke

Abstract: Studies have shown that hyperglycaemia acutely after stroke independently predicts poorer survival and independence. Whether the change in glycaemic index in the acute phase of stroke has any effect on stroke outcome is unclear. Glycated serum proteins (GSP) reflect blood glucose concentration during the preceding 2 weeks. The aim of this study is to measure the association between the change in GSP % in the first 2 weeks after stroke and outcome. 167 patients were included. 117 (70%) patients were alive at 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…24,35 Indeed, a number of studies, including ours, have reported initially positive results with unadjusted analyses and negative results after adjustment. 3,8,29,30 Our predominantly negative findings may have been due to a relative lack of power. However, if statistically significant associations are only found in large cohorts, the magnitude of the effect is likely to be small.…”
Section: Discussionmentioning
confidence: 80%
“…24,35 Indeed, a number of studies, including ours, have reported initially positive results with unadjusted analyses and negative results after adjustment. 3,8,29,30 Our predominantly negative findings may have been due to a relative lack of power. However, if statistically significant associations are only found in large cohorts, the magnitude of the effect is likely to be small.…”
Section: Discussionmentioning
confidence: 80%
“…Acute hyperglycemia following ischemic and traumatic brain injury has been shown to be associated with larger infarct volume and worse neurological outcome. 5,6,9,13,24,30,36,43,46,49 Elevated levels of advanced glycosylation end products, which quench vasodilators such as adenosine and nitric oxide, have been suggested to underlie this hyperglycemic effect. Nishikawa et al 31 identified 3 separate pathways of hyperglycemia-associated injury, all of which were blocked by limiting glucose-induced mitochondrial superoxide production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have demonstrated better outcomes in the intensive care and stroke patients with tight glycemic control. [1][2][3][4][5][6] These data suggest that identifying the hyperglycemic undergoing CEA may be useful. The authors suggest that regional blood flow compromise and small embolic events, although asymptomatic, may result in transient ischemic insults and that the hyperglycemia may affect the outcome via similar mechanisms in these patient populations.…”
Section: Commentarymentioning
confidence: 95%